1999
DOI: 10.2307/3237166
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient limitation and vegetation changes in a coastal dune slack

Abstract: . Basiphilous pioneer species are among the most endangered plant species in The Netherlands. They find most of their refuges in young coastal dune slacks, especially on the Wadden Sea islands. For the purpose of nature management it is important to know which processes control the presence of basiphilous pioneer communities, and to learn about the nature of slacks harbouring the concerning successional sequences. In a large dune slack on the Island of Terschelling, we assessed soil nutrient status and tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 32 publications
3
41
0
1
Order By: Relevance
“…Calamagrostis epigejos is a species with low requirements for both phosphorus and -like other grasses -potassium [43]. Nevertheless, according to Rebele [44] and Lammerts et al [45], the availability of phosphorus and potassium facilitates the growth of C. epigejos. Süß et al [26] observed that in some cases scarcity of nutrients might prevent vast coverage by C. epigejos.…”
Section: Discussionmentioning
confidence: 99%
“…Calamagrostis epigejos is a species with low requirements for both phosphorus and -like other grasses -potassium [43]. Nevertheless, according to Rebele [44] and Lammerts et al [45], the availability of phosphorus and potassium facilitates the growth of C. epigejos. Süß et al [26] observed that in some cases scarcity of nutrients might prevent vast coverage by C. epigejos.…”
Section: Discussionmentioning
confidence: 99%
“…Most specialised species of oligotrophic (nutrient-poor) systems, both acid and basiphilous, belong to the rare and threatened species pool (Lammerts et al 1999). The maintenance or restoration of these less eutrophicated habitats in wetlands is a paramount necessity for maintaining overall species diversity, even if very low nutrient levels decrease local species richness by selecting specialised species.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, internal nutrient sources need consideration, especially in the shallower depressions. As organic soil matter accumulates, the influence of the calcareous substrate is reduced and nutrient availability increases (Lammerts et al, 1999). In ageing dune valleys some natural eutrophication therefore occurs.…”
Section: Discussionmentioning
confidence: 99%
“…These levels are markedly exceeded in all pools, except G. In order to improve opportunities for formerly characteristic sensitive species, management should aim at restoring moderately eutrophic conditions in general, and intensifying processes that lead to small-scale habitat diversification by reducing local nutrient availability (see e.g. Jones and Etherington, 1992;Lammerts et al, 1992Lammerts et al, , 1999. Clearly, this cannot be left to naturally occurring dune processes for which this fixed and spatially constrained setting leaves very little opportunity.…”
mentioning
confidence: 99%